WANDERING WITH ARTIFICIAL INTELLIGENCE AND ITS OBSCURE LEGAL LIABILITY - Nur Fauzan, Muhammad Pasha; Amarta, Darian; Tobias, Evan; Ricardo, Vikri; G., Melania Fidela (Indonesia Law Review, 2021)
The high level of autonomy of AI will raise the problem of legal liability at some point in the future. If AI’s behaviour causes an illegal consequence, who to held liable? This article will explore the problem concerning legal liability of AI into two main discussion. The first discussion will explore the possibility of imposing legal liability of AI to human. This part will discuss various available option to solve the AI liability problem by imposing legal liability on either users or manufacturers. While the second discussion will explore the possibility of imposing legal liability of AI to AI itself. This part is a different discussion area based on experimental of legal thinking and hypothetical scenario to test the possibility of imposing legal liability on AI either as artificial person just like corporation or as natural person just like human. This article concludes that imposing legal liability on both users and manufacturer are very problematic. Meanwhile, imposing legal liability on AI itself faces a serious philosophical and sociological challenge.